ChemInform Abstract: A Novel Protocol for the One‐Pot Borylation/Suzuki Reaction Provides Easy Access to Hinge‐Binding Groups for Kinase Inhibitors. Issue 20 (April 2016) - Hooper, A.; Zambon, A.; Springer, C. J.
Abstract: An one‐pot sequence of borylation and Suzuki reaction is used for the preparation of 20 bi‐ and polyarenes, e.g. vemurafenib precursor (IIId) and analogues (V) of kinase inhibitor GDC‐0879.